2020
DOI: 10.1002/jlb.5ma1219-296r
|View full text |Cite
|
Sign up to set email alerts
|

Pitfalls in the characterization of circulating and tissue-resident human γδ T cells

Abstract: Dissection of the role and function of human γδ T cells and their heterogeneous subsets in cancer, inflammation, and auto‐immune diseases is a growing and dynamic research field of increasing interest to the scientific community. Therefore, harmonization and standardization of techniques for the characterization of peripheral and tissue‐resident γδ T cells is crucial to facilitate comparability between published and emerging research. The application of commercially available reagents to classify γδ T cells, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“… 71 Further optimization of staining protocols and antibody clone selection, which includes suitable mAbs directed against γδ T cell subsets, will help to improve immunohistological studies in the future. 72 We anticipate that interest in γδ T cell subset analysis within tumors in situ will be invigorated with innovative technologies such as fully automated high-content imaging and quantitative whole-slide imaging analysis. 73 , 74 …”
Section: Tumor-infiltrating γδ T Cells: Friends or Foes?mentioning
confidence: 99%
See 1 more Smart Citation
“… 71 Further optimization of staining protocols and antibody clone selection, which includes suitable mAbs directed against γδ T cell subsets, will help to improve immunohistological studies in the future. 72 We anticipate that interest in γδ T cell subset analysis within tumors in situ will be invigorated with innovative technologies such as fully automated high-content imaging and quantitative whole-slide imaging analysis. 73 , 74 …”
Section: Tumor-infiltrating γδ T Cells: Friends or Foes?mentioning
confidence: 99%
“…As yet, limited information is available on the TCR repertoire of γδ TILs in human tumors. Based on antibody staining with available mAbs to identify expressed TCR Vγ chains, 72 an increase in non-Vδ2 γδ T cells coexpressing Vγ2/3/4 among ascites and TIL γδ T cells compared to levels in peripheral blood was observed in ovarian cancer patients. 77 In glioblastoma multiforme, unique TCR clonotypes were identified by next-generation sequencing in intratumoral Vγ9Vδ2 γδ T cells compared to peripheral blood, suggesting specific recruitment of selected γδ T cells to the tumor site.…”
Section: Tumor-infiltrating γδ T Cells: Friends or Foes?mentioning
confidence: 99%
“…58 Similar to the results in ovarian cancer measured by flow cytometry, a co-expression of Vγ2, 3, or 4 on Vδ1 TIL is also detected by IHC in frozen sections of colon adenocarcinoma patients. 53 In contrast, an enhanced number of Vδ2 was found in glioblastoma multiforme, 75 whereas no significant difference in the percentage of Vδ1 and Vδ2 T cells was observed in prostate cancer tissue in comparison with PBL. 76 In the majority of the above described tumor entities, γδ TIL are described to be in an activated stage accompanied by an increased number of Vδ1 TIL with a T CM or T EM -phenotype and Vδ2 TIL with an T EM or TEMRA-phenotype.…”
Section: Distribution Of Tumor-infiltrating γδ T Cell Subsetsmentioning
confidence: 90%
“…52 In addition, analysis of paraffin-embedded sections from patients with Epstein-Barr virus (EBV)-associated Hodgkin's lymphoma demonstrated that most of the γδ T cells from these patients expressed Vγ9, whereas γδ T cells expressing Vγ2, 3, or 4 were nearly absent. 53 γδ T cell infiltration and correlation with patient outcome have been also demonstrated in epithelial and solid tumor cells including melanoma, colorectal, breast, pancreatic, and ovarian cancer. [54][55][56][57][58] Immunohistochemistry (IHC)-based analysis allows analysis of tumor-infiltrating γδ T lymphocytes (γδ TIL) within the tumor as well as in the context of the TME or the surrounding tissue.…”
Section: γδ T Cells In Cancermentioning
confidence: 93%
“…In the context of the proposal by Bagwell et al, we believe that optimization of the proposed antibody panel by substituting the pan-γδ T cell receptor (TCR) antibody deriving from the clone "B1" with a different clone, for example, "11F2," is essential. "B1-antibodies" may not be able to identify the entirety of the γδ T cell population when used in combination with a CD3 antibody, probably due to close proximity of the recognized epitopes causing steric hindrance (BD datasheet "clone B1", Wistuba-Hamprecht, Pawelec, & Derhovanessian, 2014;Beucke et al, 2020). Another advantage of "11F2-antibodies" is that they are known to work well in combination with additional TCR γδ antibodies such as those specific for Vδ1 (clone REA173) orVδ2 (clone 123R3).…”
mentioning
confidence: 99%